Engineering the HOMO–LUMO gap of indeno[1, 2-b]fluorene. Issue 32 (3rd August 2022) - Casares, Raquel; Martínez-Pinel, Álvaro; Rodríguez-González, Sandra; Márquez, Irene R.; Lezama, Luis; González, M. Teresa; Leary, Edmund; Blanco, Víctor; Fallaque, Joel G.; Díaz, Cristina; Martín, Fernando; Cuerva, Juan M.; et al.
Abstract : The insertion of phenyl acetylenes at the reactive positions of indeno[1, 2- b ]fluorene leads to tune its optoelectronic and magnetic properties. Furthermore, its single-molecule conductance has been investigated for the first time. Abstract : A direct, efficient and versatile strategy for the modulation of optoelectronic and magnetic properties of indeno[1, 2- b ]fluorene has been developed. 4-Substituted-2, 6-dimethylphenyl acetylene groups placed in the apical carbon of the five-membered rings lead to redshifted absorption maxima ( λ max ranging from 600–700 nm) and considerable narrowing of the HOMO–LUMO energy gap (down to 1.5 eV). Experimental and theoretical data show an increase in the diradical character ( y ) and a decrease of the singlet-triplet energy gap. Moreover, we have investigated the single-molecule conductance of the antiaromatic indeno[1, 2- b ]fluorene for the first time by including thiomethyl (-SMe) anchor groups on the phenylacetylene moiety. Conductance values one order of magnitude higher than those of a reference linear 3-ring para -phenylene ethylene have been found, despite the longer length of the S-to-S molecular junction. First principles transport calculations support this high conductance value.